PENGARUH KREATIVITAS GURU DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 9 MANDAU KABUPATEN BENGKALIS - Ratih Ayuning Chintya; Gimin Gimin; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the influence of teachers' creativity and interest in learning on student learning outcomes economic subjects in SMA Negeri 9 Mandau Bengkalis. This research use quantitative descriptive method and population in this research is student of class XI IPS which amounted to 105 people and sample obtained by using proportional random sampling technique counted 51 respondents. Data analysis techniques used are descriptive analysis, data quality test, classical assumption test, hypothesis test, multiple linear regression analysis and coefficient of determination (R2) with the help of SPSS version 16.0. The result of this research is teacher's creativity have a significant effect to student learning result which obtained tcount 4,692> ttable 2,011 and significant value 0,000 <0,05. Interest in learning significantly influence student learning outcomes where obtained tcount 2.589> ttable 2.011 and significant value 0.013 <0.05. Simultaneously there is a significant influence between teacher creativity and student learning interest with learning outcomes where obtained value fhitung 30,750> ftabel 3,191 and significant value 0,000 <0,05. The multiple linear regression equation obtained in this research is Y = 56,515 + 0,157X1 + 0,265X2. This means that if the creativity of teacher (X1) and interest in learning (X2) is zero (0) then the learning result (Y) is 56,515 and every increase of teacher creativity will increase student learning outcomes by 0,157 and every increase of interest learn then will improve student learning outcomes by 0,265. The result of research of coefficient of determination (R2) found that percentage contribution contribution of teacher creativity variable and learning interest to learning result equal to 56,2% and the rest counted 43,8% influenced by other variable not explained in this research. Key Words: Teachers’ Creativity, Learning Interest, Learning Outcomes